2020
DOI: 10.1155/2020/2374650
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Internal Limiting Membrane Flap Technique versus Internal Limiting Membrane Peeling for Vitrectomy in Highly Myopic Eyes with Macular Hole-Induced Retinal Detachment: An Updated Meta-Analysis

Abstract: Background. The aim of this meta-analysis was to compare morphological and functional outcomes between vitrectomy with the inverted internal limiting membrane (ILM) flap technique and vitrectomy with internal limiting membrane peeling in highly myopic eyes with macular hole- (MH-) induced retinal detachment (MHRD). Methods. The PubMed, Web of Science, Embase, and Cochrane Library databases were comprehensively searched from inception to November 10, 2019, for published studies comparing the two techniques for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Therefore DM might cause delayed or non-existent functional recovery after MHS, as it causes disorders in the vascular structure. Inverted flap technique is preferred in traumatic MH, MH with RD, MH in high myopia or positioning distress, besides seemed does not improve postoperative BCVA, as reported in previous studies (26)(27). Since all of our patients had idiopathic FTMH, and none of the patients had positioning distress, we used PPV with ILM peeling technique instead of the inverted flap technique.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore DM might cause delayed or non-existent functional recovery after MHS, as it causes disorders in the vascular structure. Inverted flap technique is preferred in traumatic MH, MH with RD, MH in high myopia or positioning distress, besides seemed does not improve postoperative BCVA, as reported in previous studies (26)(27). Since all of our patients had idiopathic FTMH, and none of the patients had positioning distress, we used PPV with ILM peeling technique instead of the inverted flap technique.…”
Section: Discussionmentioning
confidence: 75%
“…ILM peeling with foveal retention avoided damaging central Müller cells, which were connected tightly to the photoreceptor cells, therefore reducing the risk of postoperative macular alterations [ 27 ]. The inverted ILM flap technique was initially used to treat MHs, and proved to be effective in achieving higher closure rates of the large macular holes [ 28 ] and improving anatomical and functional outcomes in myopic macular holes and high myopic macular holes accompanied by retinal detachment [ 21 , 22 ]. A recent study indicated combining fovea-sparing ILM peeling and inverted ILM flap technique further reinforced the foveal structure and decreased the risk of FTMH formation in MF patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inverted ILM flap technique demonstrated an improvement in anatomic outcomes and functional outcomes for patients with myopic macular holes (MH) and high myopic macular hole induced retinal detachments [ 21 , 22 ]. A flap of ILM covering the surface of MH stimulated the proliferation of glial cells and contributed to the restoration of foveal architecture as a scaffold [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is achieved by removal and release of the adhesion of the posterior vitreous cortex, as well as the elements that generate the tangential traction, through the removal of epiretinal fibroglial tissue and internal limiting membrane [3]. These mechanisms include the generation of a tissue scaffold for the growth of reparative tissue through the addition of internal limiting membrane flaps [4,5], lens capsule [6], amniotic membrane [7], and neurosensory retina transplants [8], as well as compensatory scleral ectasia by volume occupation or opposition (macular indentation) [9]. We conceived and carried out a variant of the endoocular technique, which seeks to not only take advantage of these principles but also to generate additional mechanisms based on the properties of the tissues used and their arrangement.…”
Section: Discussion/conclusionmentioning
confidence: 99%